Records Committee review for rare bird sighting of Iceland Gull at Lake MacBride, 1993 - Fuller, James Let al (1993)
Records Committee review of an Iceland Gull at Lake MacBride in Johnson County, IA on April 16, 1993. Includes a record review document with votes and a documentation form submitted to the committee. Epson - sheet feed